Metabolic Disruptions in Zebrafish Induced by α-Cypermethrin: A Targeted Metabolomics Study - Hang-Ji Ok; Ji-Woo Yu; Jung-Hoon Lee; Eun-Song Choi; Jong-Hwan Kim; Yoonjeong Jeon; Won Noh; Sung-Gil Choi; Jeong-Han Kim; Min-Ho Song; Ji-Ho Lee (Toxics, 2025)
The widespread application of pesticides in agriculture has raised increasing concerns regarding their ecological impact, particularly in aquatic environments. Among these, α-cypermethrin, a highly active isomeric form of cypermethrin, has been extensively used due to its potent insecticidal efficacy and low mammalian toxicity. However, its toxicity to non-target aquatic organisms remains insufficiently understood at the metabolic level. In this study, a targeted metabolomics approach was employed to investigate the biochemical effects of α-cypermethrin in adult zebrafish. Acute toxicity was first determined to establish sublethal exposure concentrations (0.15 µg/L and 1.5 µg/L), followed by a 48 h exposure under a controlled flow-through system. GC-MS/MS-based analysis quantified 395 metabolites, and multivariate statistical models (principal component analysis (PCA) and partial least square-discriminant analysis (PLS-DA)) revealed clear dose-dependent metabolic alterations at two time points. Pathway analysis identified disruptions in glycolysis, glycerolipid metabolism, amino acid turnover, and glutathione pathways. Notably, glutamate depletion and associated reductions in GABA (4-Aminobutanoate) and TCA (Tricarboxylic acid) cycle intermediates suggest oxidative stress-induced metabolic bottlenecks. These results provide mechanistic insights into α-cypermethrin-induced toxicity and demonstrate the utility of metabolite-level biomarkers for environmental monitoring. This study contributes to a systems-level understanding of how sublethal pesticide exposure affects vertebrate metabolism, offering a basis for improved ecological risk assessment and pesticide regulation.